Corruption, political instability and economic development in the Economic Community of West African states (ECOWAS): Is there a causal relationship? - Nurudeen Abu; Mohd Zaini Abd Karim; Mukhriz Izraf Azman Aziz (Contemporary Economics, 2015)
Despite the abundant research on economic development, corruption and political instability, little research has attempted to examine whether there is a causal relationship among them. This paper examines the causal relationship among corruption, political instability and economic development in the ECOWAS using the Granger causality test within a multivariate cointegration and error-correction framework for the 1996 - 2012 period. The findings indicate that political instability Granger-causes economic development in the short term, while political instability and economic development Granger-cause corruption in the long term. In addition, we employed the forecast error variance decomposition and impulse response function analyses to investigate the dynamic interaction between the variables. The results demonstrate positive unidirectional Granger causality from political instability to economic development in the short term and positive unidirectional Granger causality from political instability and economic development to corruption in the long term in ECOWAS countries. Thus, ECOWAS governments should employ policies to promote political stability in the region.
Keywords: E21; 330; Corruption; Political instability; Economic development; ECOWAS